(untitled) (Journal of Educational Sciences, 2019)
The training of qualified young professionals is a priority for the higher education. Therefore it is needed to improve training at the university competence of teachers that correspond to the requirements of the time. The article are reveals the essence of a competent approach to the training of future teachers of primary education and addresses the problem of the formation of substantive competencies as a condition for the quality training of teachers for professional activities. The authors reveal the specificity and content of subject specific competences which should possess a primary school teacher. The levels of formation of the substantive competencies are developed on the basis of B.Bloom’s taxonomy of the educational purposes and the specifics of the specialty. The results of experimental studies to identify students level of the development of substantive competences in the process of teaching practice on the 3rd course are represented. They show a need for in-depth work on the formation of the desired competence in further study courses. In this regard to the content of the educational and methodological complexes of the studied disciplines has been revised based on the recommendations of employers and practice instructors. The results of industrial (pedagogical) practice on the 4th course have proved the effectiveness of the updates in the implementation of the practice-oriented approach to the educational process of the university at form the substantive competencies for the students. Key words: competence, professional competencies, substantive competences, pedagogical practice, teaching and educational process.